Assessment Model for Communication Maturity Levels of Construction Companies - Bavunoğlu, Zeynep; Günaydın, Hüsnü Murat (Izmir Institute of Technology, 2014)
Communication management systems are vital parts of organizational development and performance. Organizations have complex characteristics including decision making, information aggregation, management control, career concerns, goal setting and vertical and horizontal communication. In recent years, it has been found out that communication has an important effect on all these characteristics. But quantifying the effectiveness of the communication is difficult because it has many non-measurable variables. An effective communication can increase the level of effectiveness of the organization and the level of the effectiveness of communication system can be assessed by using maturity models. A maturity model describes the activities of processes and it impacts the performance of the organization. To find out the structure and maturity level of the communication system in a construction company, the Communication Capability Maturity Model (CCMM) is developed and its levels for communication maturity. To define a maturity level for a construction company, some variables of communication are measured as speed, the purpose, spread, clarity, shortness, scope and the other variables. The developed methodology uses a questionnaire survey. Survey has two parts; (1) organizational communication system and (2) emotions/moods of the employees. The results and analysis show that developed CCMM working properly and there are strong interdependencies between the variables (i.e. organizational communication system and moods, information, organization, team, individual and product). There is a negative moderate high correlation between communication capability maturity level (CCML) and negative moods. There is a moderate high correlation between the communication capability maturity level and level of emotional management behavior.
İnşaat Şirketlerinin İletişim Olgunluk Seviyelerini Değerlendirme Modeli
Thesis (Doctoral)--İzmir Institute of Technology, Architecture, İzmir, 2014
Full text release delayed at author's request until 2017.12.26
Includes bibliographical references (leaves: 102-105)
Text in English; Abstract: Turkish and English
Keywords: Construction projects; Project management; Communication management